4D bioprinting of smart polymers for biomedical applications: recent progress, challenges, and future perspectives - Arif, Zia Ullah; Khalid, Muhammad Yasir; Zolfagharian, Ali; Bodaghi, Mahdi (Reactive & functional polymers, 2022)
4D bioprinting is the next-generation additive manufacturing-based fabrication platform employed to construct intricate, adaptive, and dynamic soft and hard tissue structures as well as biomedical devices. It is achieved by using stimuli-responsive materials, especially shape memory polymers (SMPs) and hydrogels, which possess desirable biomechanical characteristics. In the last few years, numerous efforts have been made by 4D printing community to develop novel stimuli-responsive polymeric materials by considering their biomedical perspective. This review presents an up-to-date overview of 4D bioprinting technology incorporating bioprinting materials, functionalities of biomaterials as well as the focused approach towards different tissue engineering and regenerative medicine (TERM) applications. It includes bone, cardiac, neural, cartilage, drug delivery systems, and other high-value biomedical devices. This review also addresses current limitations and challenges in 4D bioprinting technology to provide a basis for foreseeable advancements for TERM applications that could be helpful for their successful utilization in clinical settings. [Display omitted] •A compendium review of 4D bioprinting technology.•Development of scaffolds for tissue regeneration through 4D bioprinting.•Fabrication of biomedical devices by stimuli-responsive polymers and hydrogels.•Addressing current limitations and challenges in 4D bioprinting.